A forest in the city - Curtis, Andrea (ThinkCities., 2020)
Examines the urban forest, exploring it from the tops of trees to the bottom of their roots beneath city streets. Describes the problems that city trees face, including cement, poor soil, and disease, and the benefits of trees such as beauty, shade, and a challenge to climate change. Includes a glossary, a list of activities, and selected resources for additional information.